Enhancing Digital Literacy for Business Development in Micro, Small, and Medium Enterprises (MSMEs) through Banking Initiatives at the Rural Level in Indonesia - Rujitoningtyas, Choirun Nisaa; Nugraha, Erik Ridha; Laksana, Himawan Dwi; Apriyanto, Yugi; Dewi, Nurma Gupita (Universitas YPPI Rembang, 2024)
The advancement of digital technology has presented significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach and enhance operational efficiency. However, limited digital literacy, particularly in rural areas of Indonesia, poses a critical barrier to leveraging these opportunities. This study explores the role of banking initiatives in enhancing digital literacy among rural MSMEs, focusing on their impact on business development. Through a mixed-methods approach involving surveys and interviews with MSME owners, banking representatives, and local stakeholders, the study identifies key challenges in digital adoption, such as lack of access to technology, inadequate training, and low awareness of digital tools. It also highlights successful banking-led programs, including digital financial literacy workshops, mobile banking services, and partnerships with local governments. The findings demonstrate that targeted banking initiatives significantly improve MSMEs' ability to integrate digital tools into their operations, leading to increased revenue, broader market access, and improved financial management. This paper concludes by emphasizing the importance of collaborative efforts between banks, governments, and community organizations to sustain digital literacy efforts and foster rural MSME growth in IndonesiaKeywords: Digital Literacy, Micro, Small, and Medium Enterprises (MSMEs), Business Development, Rural Banking Initiatives.